1986
DOI: 10.1007/bf00215889
|View full text |Cite
|
Sign up to set email alerts
|

Formation of apical tubules from large endocytic vacuoles in kidney proximal tubule cells during absorption of horseradish peroxidase

Abstract: Using horseradish peroxidase (HRP) as a tracer, we have investigated if the so-called apical tubules (AT) in the kidney proximal tubule cells are directly involved in the endocytic process by carrying the tracer into the cells, or if they are derived from the intracellular membrane compartments. Rat kidney was fixed by vascular perfusion at different time intervals after intravenous injection of HRP and prepared for electron microscopy. An analysis revealed that 0.5 min after injection, invaginations of the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
1
33
0
Order By: Relevance
“…In particular, the anastomosing network of DAT, an organelle that has a characteristic spinelike protein coat covering its inner surface and mostly lacks an external clathrin coat (8), was absent (Figure 4, a and a'). HRP, a marker of fluid phase endocytosis, was intravenously applied to study alterations of this process with respect to megalin deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the anastomosing network of DAT, an organelle that has a characteristic spinelike protein coat covering its inner surface and mostly lacks an external clathrin coat (8), was absent (Figure 4, a and a'). HRP, a marker of fluid phase endocytosis, was intravenously applied to study alterations of this process with respect to megalin deficiency.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested based on ultrastructural tracer studies that the AT originate, by budding off, from the large endocytic vacuoles and transport endocytosed membrane material back to the apical cell surface (membrane recycling) (2,11,12,15,18). The view that the AT play a role in membrane recycling has been supported by enzyme cytochemistry that the reaction products for acid and alkaline phosphatase are present in both the AT and the apical cell surface of the absorptive cells of rat yolk sac endoderm (42).…”
Section: Discussionmentioning
confidence: 99%
“…Recent ultrastructural tracer studies have suggested that the AT of these epithelia have a role in recycling of the apical plasma membrane during the process of endocytosis (2,11,12,15,18). The AT originate, by budding off, from the large endocytic vacuoles and transport endocytosed membrane material back to the apical cell surface (membrane recycling).…”
mentioning
confidence: 99%
“…Three types of tubule-vesicular components were observed by transmission electron microscopy. One is a component belonging to an endocytic apparatus including intermicrovillous membrane invaginations that are decorated with clathrin coat lining over the cytoplasmic surface of the invaginating region, clathrin-coated vesicles, and vacuolar early sorting endosomes (Hatae et al 1986a). This component was observed in the WT, Ar K/K , and Esr1 K/K efferent ductules (Fig.…”
Section: Electron Microscopic Examinationsmentioning
confidence: 98%